Valued learning experiences of early career and experienced high-performance coaches - Mallett, C. J.; Rynne, S. B.; Billett, S. (Physical Education and Sport Pedagogy, 2016)
Background and purpose: This paper attempts to move the discussion of high-performance coach development from an examination of coaches' volume of experiences towards a consideration of the contribution of the learning experiences that coaches have reported throughout their careers. Furthermore, a discussion of proximal and distal guidance in the development of coaches was investigated. We examined the kinds of learning experiences within the framework of workplace learning and specifically the situated nature of learning and the view that learning occurs through social participation.